PSA I love You: Prostate Cancer Screening in Ireland - Keane, Eimear (Trinity Student Medical Journal, 2015)
Ireland has the second highest rate of prostate cancer (PCa) in Europe and this is largely due to the increased use of PSA testing in Ireland in recent years. Rapid Access Prostate Cancer Clinics (RAPC) were introduced in 2009, in order to increase the organisation and efficiency of PCa diagnosis in Ireland. The use of PSA as a screening tool is controversial. At present, there is no evidence for the introduction of widespread, population-based screening for PCa. Two large randomised studies which evaluated the efficacy of PSA testing are examined in this review. These are the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) and The European Randomised Study for Prostate Cancer (ERSPC). These studies demonstrated conflicting results. The PLCO reported that there was no evidence that PSA screening reduced PCa-related mortality, while the ERSPC showed PSA screening was associated with a 21% decrease in PCa related mortality. Following the publication of these trials, the European Association of Urology and the American Urology Association produced new PCa screening guidelines. These guidelines advised against widespread screening programmes but recommended PSA testing in men who met certain criteria (based on age, life expectancy and other risk factors). In Ireland, there are currently very little national guidelines in relation to PCa screening. However, much opportunistic testing occurs and patients often request PSA tests in a GP setting. National guidelines for PSA screening, which are in line with the AUA (American Urology Association) and EAU (European Association of Urology) guidelines, need to be introduced in order to prevent overtreatment and over-diagnosis of asymptomatic prostate cancer.